2018
DOI: 10.3390/s18103423
|View full text |Cite
|
Sign up to set email alerts
|

HCV Detection, Discrimination, and Genotyping Technologies

Abstract: According to the World Health Organization (WHO), 71 million people were living with Hepatitis C virus (HCV) infection worldwide in 2015. Each year, about 399,000 HCV-infected people succumb to cirrhosis, hepatocellular carcinoma, and liver failure. Therefore, screening of HCV infection with simple, rapid, but highly sensitive and specific methods can help to curb the global burden on HCV healthcare. Apart from the determination of viral load/viral clearance, the identification of specific HCV genotype is also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 127 publications
(124 reference statements)
0
30
0
Order By: Relevance
“…Moreover, a number of clinical practices have shown that the validation of HCV subtype plays a crucial role in determining the appropriate treatment for HCV. Thus, various methods for HCV genotyping have been developed (19). The present study successfully mitigates some of the problems inherent in HCV genotyping by using RT-qPCR.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, a number of clinical practices have shown that the validation of HCV subtype plays a crucial role in determining the appropriate treatment for HCV. Thus, various methods for HCV genotyping have been developed (19). The present study successfully mitigates some of the problems inherent in HCV genotyping by using RT-qPCR.…”
Section: Discussionmentioning
confidence: 97%
“…[ 3 ] There are several techniques used to HCV GT determination in the clinical practice, including real-time PCR, line-probe assay, heteroduplex mobility analysis, restriction fragment length polymorphism. [ 10 , 11 , 16 ] The currently available commercial techniques for HCV GT 1 failed in 2% to 16% patients. [ 16 , 17 ] In a large CHC cohort of 8,945 patients from phase II/III DAAs clinical trials, Tania Welzel [ 10 ] et al compared HCV GT and subtypes with INNO-LiPA 2.0 vs amplicon sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…[ 10 ] Hence, the sequence analysis is still the golden standard method for HCV determination, but due to the longer time and higher cost for test, and required professional equipment, the widespread application for this technology was limited. [ 10 , 11 ] Currently, pangenotypic DAAs are available in numerous countries, the use of which should be prioritised because they achieve high treatment efficacy across all 6 major HCV GTs. Treatment with pangenotypic DAAs can be initiated without determination of the GT and subtype in the regions where GT test is not available and/or not affordable, or to simplify therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatitis C is an infective illness induced by the hepatitis C virus (HCV), which is a viral RNA of the family Flaviviridae. When HCV infection is screened by simple and rapid techniques with high sensitivity and specificity, it can assist to control the encumbrance on HCV health care globally [ 74 ]. Fan et al.…”
Section: Application Of Carbon Nanomaterials For Viral Diagnosismentioning
confidence: 99%